Implementation of the Cash Revenue System: A Case Study in the Local Government Task Forces’ Units of North Sumatera Province, Indonesia - Muda, Iskandar; ., Muhammad Safri Lubis (Information Management and Business Review, 2014)
Based on the central government regulations; No. 32/2004 and No. 33/2004, a reform in governance and public sector activities has been suggested as well a new paradigm shaped in the development and management of the local financial system. The earlier adoption of the government regulation (PP) No. 58/2005 had been enhanced with the issuing of the Ministry of Home Affairs’ Regulation (Permendagri) No. 59/2007 which lays out comprehensive guidelines for the implementation of the administrative and financial accounting subject. In this Permendagri’s No. 59/2007 guidelines of financial management, by definition, the accounting system is used as a series of procedures ranging from the process of data collection, recording, summarizing, up to financial reporting responsibilities in the budget implementation framework. The model data structure is designed to give a high degree of accuracy and a higher relevance in the development of the accounting information system, without being distracted by the application code changes. The descriptive analysis adopted in this study uses both tools of the visual basic program and database of Microsoft SQL designs. The programming part is to present the results of the local government’s manual finance report into several generated computerized systems. In preparing the financial statements, it is deemed sufficient to create one format followed by the transaction journal which automatically posts directly the generated processing and financial reports. These courses will greatly assist in the preparation of the financial statements. By having such reliable information technology support, the financial governance rules contained in Permendagri are able to ensure the effectiveness of the internal control systems’ design.